A Comparative Study of Mini-FLOTAC With Traditional Coprological Techniques in the Analysis of Cetacean Fecal Samples - Marcer, Federica; Cassini, Rudi; Parisotto, Nancy; Tessarin, Cinzia; Marchiori, Erica (Frontiers in Veterinary Science, 2022)
Free-ranging cetaceans are considered sentinels for the marine ecosystem's health. New and non-invasive methods have been set up for the collection of fecal samples from free-ranging big whales at sea, permitting to gain an excellent epidemiological picture of parasitic infections in wild populations. To select the best protocol to be used for copromicroscopic examination in cetaceans stool samples, we evaluated the sensitivity of two commonly used techniques, i.e., a sedimentation-floatation method and the Mini-FLOTAC through validation by helminth isolation from the digestive tract. For this aim, gastrointestinal content and fecal samples were collected during necropsy from 44 cetaceans, including bottlenose dolphins (Tursiops truncatus), striped dolphins (Stenella coeruleoalba), sperm whales (Physeter macrocephalus), Risso's dolphins (Grampus griseus), Cuvier's beaked whales (Ziphius cavirostris), pilot whale (Globicephala melas), and fin whales (Balaenoptera physalus). Helminths were recovered through washing and filtering of the gastrointestinal contents and morphologically identified. Copromicroscopic examinations were performed on formalin-preserved fecal samples, using a sodium nitrate, sodium thiosulphate, and sucrose solution (s.g. = 1.450) for both methods. Helminths belonging to 9 taxa (i.e., the trematodes Synthesium tursionis, Synthesium delamurei, Campula palliata, Braunina cordiformis, Pholeter gastrophilus, the nematode Anisakis sp., cestodes of the family Tetrabothriidae and the acanthocephalan Bolbosoma sp.) were isolated. Eggs referable to the same taxa, with the exception of cestodes, were found in copromicroscopic analyses. Sensitivity of the Mini-FLOTAC method appeared higher or equal for all taxa, proving superior to the sedimentation-flotation method for the detection of all except Anisakis sp. The concordance of the two tests indeed revealed a moderate to perfect agreement (kappa values 0.42–1). Not excluding the limitations inherent to the techniques themselves, explanations for false-negative results at copromicroscopy could be linked to parasite-related factors, including prepatent infections, low parasitic burdens, or intermittent egg shedding. Notwithstanding these limitations, this study evidenced that the Mini-FLOTAC protocol approximates more accurately the composition of the gastrointestinal helminthic community of cetaceans from copromicroscopic examination, providing at the same time a quantitative estimation.